(untitled) (Research, Society and Development, 2020)
Introduction: Menopause marks the end of the reproductive cycle, is described by complete stop of menstruation after a period of 12 consecutive months. It occurs naturally among women with a mean age of 45 to 60 years or because of medical interventions. Urinary Incontinence (UI) may be due to aging itself and climacteric may be one of the risk factors for this dysfunction. The aim of the study is to analyze the effects of physiotherapy on UI in menopausal women. Methodology: The study is a literature review using as descriptors, urinary incontinence, menopause, pelvic floor, in the data bases Lilacs, Scielo, Medline, Pubmed. Results: UI affects 30 to 60% of women during menopause, which negatively compromises quality of life. It was analyzed that physiotherapy for menopausal women helps in improving signs and symptoms, such as, nocturia, urgency, urge-incontinence. Among the resources used in the treatment of UI stands out electrostimulation, surgical treatment, hormonal therapy (TH) with estrogen and the training of pelvic floor muscles (MAP), helping to reduce UI. Conclusion: pelvic physiotherapy is effective in UI treatments, both to reduce and to bring improvement of menopausal symptoms.